Les voyageurs anglais en Irlande au XVIIIe siècle - Claire Dubois (Revue LISA)
This paper intends to study the representations of Ireland in English travel narratives in the 18th century. After the Ulster Rebellion in 1641, very few travellers went to Ireland. All the narratives published in the 18th century aimed at confirming the stereotype of the idle, rebellious Irishman. When the fear of a possible Catholic uprising gradually faded away, new travellers came to Ireland to observe Irish barbarism with their own eyes. Their travels to Ireland did not always confirm the preconceived ideas they held about the country. A re-evaluation of Ireland thus developed, Irish barbarities being no longer the object of hatred but of benevolent interest.